1986
DOI: 10.1146/annurev.ne.09.030186.001513
|View full text |Cite
|
Sign up to set email alerts
|

Linkage Between Axonal Ensheathment and Basal Lamina Production by Schwann Cells

Abstract: The availability of several methods for the preparation of SCs free of other cell types has allowed recent experimentation providing new insights into the capacity of SCs to synthesize, release, and organize extracellular matrix materials, particularly those of the basal lamina. When these SC populations are combined in tissue culture with pure populations of neurons capable of directing SC function (without fibroblasts), new aspects of interrelationships between these cell types have come to light. In this br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
121
1
3

Year Published

1996
1996
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(128 citation statements)
references
References 0 publications
3
121
1
3
Order By: Relevance
“…The axon signals for regulating Schwann cell differentiation are known to include both proteins encoded by the neuregulin gene (NRG) signaling through the erbB family of receptors, adhesion molecules such as L1 and N-cadherin and neurotrophic factors such as brainderived neurotrophic factor (BDNF) (34)(35)(36)(37). It has been suggested that cell adhesion molecules on the axon surface as well as signals from the extracellular matrix and neurotrophins are also required for myelination to proceed efficiently and accurately.…”
Section: Discussionmentioning
confidence: 99%
“…The axon signals for regulating Schwann cell differentiation are known to include both proteins encoded by the neuregulin gene (NRG) signaling through the erbB family of receptors, adhesion molecules such as L1 and N-cadherin and neurotrophic factors such as brainderived neurotrophic factor (BDNF) (34)(35)(36)(37). It has been suggested that cell adhesion molecules on the axon surface as well as signals from the extracellular matrix and neurotrophins are also required for myelination to proceed efficiently and accurately.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the ECM molecules of the basal lamina are crucial for both axonal elongation and remyelination (Bunge et al, 1986;Reichardt and Tomaselli, 1991). Schwann cells react to changes in the composition of the ECM after nerve lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Schwann cell interaction with ECM as a prerequisite for myelination is well established (Bunge et al, 1986). Several matrix protein-receptor interactions that are important for Schwann cell myelination have been described.…”
Section: Discussionmentioning
confidence: 99%